Formation of the labor payment system at the enterprise - O. YURCHENKO; O. SVYRYDA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2023)
The purpose of the article is to study the theoretical and methodological foundations of the formation of the labor payment system at a modern enterprise.The article highlights the essence of wages, characterizes its functions, and summarizes approaches to the organization of wages at enterprises. The main elements of the wage system model are defined. It is noted that the selection and application of acceptable forms of remuneration requires taking into account a significant number of economic, social and psychological factors, as well as the effective functioning of personnel management subsystems at the enterprise, such as labor regulation and evaluation of personnel performance.Emphasis is placed on the need to introduce labor regulation as a condition for ensuring the connection of wages with the final results of work. A conclusion was made about the need to properly build a bonus subsystem at the enterprise, especially when applying time-bonus or unit-bonus forms of remuneration. Variants of establishing award conditions and award sizes offered by domestic scientists were considered. Emphasis is placed on the mandatory inclusion of bonus conditions in the collective agreement or the development of the Bonus Regulations.It is noted that the application of most new (combined) forms of labor remuneration (non-tariff, point-based, bonus, grading) requires the presence of an effective subsystem for evaluating personnel and the results of their work at the enterprise.The list of indicators used to evaluate the effectiveness of the personnel remuneration system formed at the enterprise is considered.It was concluded that the development and introduction of an effective model of remuneration of employees leads to an increase in the labor productivity of the personnel, the solution of the problem of social and labor conflicts, and the achievement of the goals set by the enterprise in its development.